Economies of scale, bulk discounts, and liquidity constraints: comparing unit value and transaction level evidence in a poor country - Gibson, John; Kim, Bonggeun (Review of economics of the household, 2018)
We examine bulk discounts, which are claimed to explain the Deaton and Paxson puzzle about household size and food demand, and which may matter to household behavior studied in other literatures. Most previous studies use unit values, which are subject to several biases and reflect economizing choices made by households, so may not reliably estimate the bulk discount schedule. Instead, individual transaction records in household expenditure diaries are used, which report expenditure, quantity, brand, unit size and number purchased per transaction. The bulk discount schedule is estimated for four foods (rice, canned meat, canned fish and chicken) that make up one-third of the total food budget in a survey in urban Papua New Guinea. For each food we use the dominant brand(s) so there is no quality variation and the estimated price schedule only reflects discounts due to variations in purchase quantity. All foods have precisely measured but small elasticities of unit price with respect to quantity purchased.